PENGARUH CSR DENGAN DIREKSI WANITA SEBAGAI VARIABEL MODERASI TERHADAP TAX AVOIDANCE (Studi pada Perusahaan Sektor Manufaktur dan Sektor Energi yang Terdaftar di BEI pada Tahun 2019-2023) - Risma Sandi Allaauddina; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2026)
This study aims to determine the impact of CSR on tax avoidance and the role of women directors as a moderating variable in manufacturing and energy companies listed on the Indonesia Stock Exchange from 2019 to 2023. The variables used are the dependent variable (tax avoidance), independent variable (CSR), moderating variable (women directors), and control variables (company size, leverage ratio, and return on assets). This study utilizes secondary data. The sample consists of 421 manufacturing and energy sector companies selected through purposive sampling, with data obtained from audited annual reports, sustainability reports, and financial statements published on the IDX and Bloomberg databases. The analytical technique employed is multiple linear regression analysis, with testing conducted using classical assumption tests.The results of this study indicate that CSR has a positive but not significant effect on tax avoidance behavior. Furthermore, the presence of female directors does not moderate the relationship between CSR disclosure and tax avoidance.